Global prevalence and antibiotic resistance in clinical isolates of Stenotrophomonas maltophilia: a systematic review and meta-analysis - Banar, Maryam; Sattari-Maraji, Azin; Bayatinejad, Ghazal; Ebrahimi, Elahe; Jabalameli, Leila; Beigverdi, Reza; Emaneini, Mohammad; Jabalameli, Fereshteh (Frontiers in Medicine, 2023)
Stenotrophomonas maltophilia is a less-known environmental opportunistic bacterium that can cause broad-spectrum infections. Despite the importance of this bacterium as an emerging drug resistance opportunistic pathogen, a comprehensive analysis of its prevalence and resistance to antibiotics has not yet been conducted. A systematic search was performed using electronic databases (MEDLINE via PubMed, Embase, Scopus, and Web of Science) up to October 2019. Out of 6770 records, 179 were documented in the current meta-analysis according to our inclusion and exclusion criteria and 95 studies were enrolled in the meta-analysis. Present analysis revealed that the pooled prevalence of S. maltophilia in the world was 5.3 % [95% CI: 4.1-6.7%], with a higher prevalence in Western Pacific Region [10·5%; 95% CI:5·7-18·6%] and less in American regions [4·3%; 95% CI: 3·2-5·7%]. The subgroup meta-analysis revealed that the prevalence rate of S. maltophilia infection after 2010 (7·7% [95% CI: 5·3-11·1%]) was higher than before this time (4·4% [95% CI: 3·2-5·6%]). Based on our meta-analysis the highest antibiotic resistance rate was against cefuroxime [99·1%; 95% CI: 97·3-99·7%], while the lowest resistance was correlated to minocycline [4·8%; 95% CI: 2·6-8·8%]. The results of this study indicated that the prevalence of S. maltophilia infections increasing since 2010. Comparing the antibiotic resistance of S. maltophilia before and after 2010, the increasing trend of the resistance of some antibiotics such as tigecycline, ticarcillin-clavulanic acid was shown. However, trimethoprim-sulfamethoxazole is still considered an effective antibiotic for treating S. maltophilia infections.